RFID implementation on domestic animals - Tan, Tit King (2010)
Due to the adaption from media and television, we often have a perspective about farms where it is a place without advanced technologies. Works in the farm are carried out manually without the help of machines. For example, counting the animals, taking out which animal for medication and many more other jobs in a farm. As real as it is shown, our country, Malaysia, is slightly being left out from the advances of technology where animal breeding are still being done manually and without any computers that can help to increase the productivity and efficiency in breeding. This project is actually to help breeders have an easier way in managing and monitoring their own animals. In this project, sheep breeding are taken as the case study. A RFID environment system will be implemented on a sheep farm to detect the correct amount of sheep present, monitoring each sheep and also to give breeders an automated way of managing its farm. Therefore, is it hoped that with the implementation of RFID on farms, would help breeders to increase the productivity and efficiency in breeding.